2019
DOI: 10.14434/josotl.v19i4.24167
|View full text |Cite
|
Sign up to set email alerts
|

‘If They Don’t Care, I Don’t Care’: Millennial and Generation Z Students and the Impact of Faculty Caring

Abstract: This article draws on a qualitative study of 31 Millennial and Generation Z students to examine the meaning of teacher "caring" in a higher education context. Prior research clearly documents the importance of caring to student engagement, although much of that scholarship focuses on secondary schooling. Research also examines the changing demographics of higher education and new expectations brought to college classrooms by Millennials and others. In this article, we connect the existing research on caring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 23 publications
1
54
1
2
Order By: Relevance
“…The Miller and Mills (2019) article begins by affirming the well‐established centrality of caring to effective teaching in primary and secondary school settings (e.g., Finn, Schrodt, Witt, Elledge, Jernberg, & Larson, 2009). The article then quickly moves to introducing the more recent scholarship that has begun to call attention to the importance of faculty caring to students’ learning and success in higher education (e.g., Meyers, 2009; Slate, LaPrairie, Schulte, & Onwuegbuzie, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Miller and Mills (2019) article begins by affirming the well‐established centrality of caring to effective teaching in primary and secondary school settings (e.g., Finn, Schrodt, Witt, Elledge, Jernberg, & Larson, 2009). The article then quickly moves to introducing the more recent scholarship that has begun to call attention to the importance of faculty caring to students’ learning and success in higher education (e.g., Meyers, 2009; Slate, LaPrairie, Schulte, & Onwuegbuzie, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The article then quickly moves to introducing the more recent scholarship that has begun to call attention to the importance of faculty caring to students’ learning and success in higher education (e.g., Meyers, 2009; Slate, LaPrairie, Schulte, & Onwuegbuzie, 2011). According to Miller and Mills (2019), this interest in the impact of caring faculty in higher education has emerged from both rising efforts to retain an increasingly diverse undergraduate student body and questions regarding the unique perspectives and needs of the newest generations of college students, Millennials and Generation Z. The Millennial and Generation Z students are often perceived as needing more attention and care than previous generations (Goldman and Martin, 2016; Varallo, 2008), and as higher education institutions strive to recruit, retain, and graduate these students, questions about what these students need to succeed is garnering center stage attention in numerous institutions (Mintz 2019; Pelletier 2019), including my home institution, the University of Illinois at Urbana‐Champaign.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that de-motivated students in the classroom will be less likely to engage in other resources offered. [8] This suggests that merely changing office hours from faceto-face to virtual will do little to increase student use of this resource. [9] Benefits from faculty-student interactions are numerous, and students need to be cognizant of these benefits.…”
Section: Implication For Studentsmentioning
confidence: 99%
“…Students of this generation are accustomed to high levels of guidance, oversight, high use of technology, coupled with desires to interact with peers in collaborative ways. [8] Manipulating generational predispositions' physiognomies will increase the high-impact strategy of faculty-student interaction. Successful engagement of students through faculty-student contact requires fluidity in strategies and educational culture.…”
Section: Implication For Studentsmentioning
confidence: 99%